IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN IPS EKONOMI SISWA KELAS X DI SMA NEGERI 4 KOTA BIMA TAHUN AJARAN 2023/2024 - Fitriani Fitriani; Fadilah Try Mursyid; Mukhlis Mukhlis (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2025)
This research aims to determine the implementation of the independent curriculum at SMA Negeri 4 Bima City for the 2023/2024 academic year. This research uses qualitative research conducted at SMA Negeri 4 Bima City with a descriptive research design. The data collection techniques are carried out by observation, interviews and documentation. The research results show that the strategy for implementing the independent curriculum is by holding training activities or In House Training (IHT) workshops, regarding the implementation of the independent curriculum in forming learning tools for Learning Achievements (CP), holding workshops for implementing differentiated learning and carrying out training preparations for the Strengthening Pancasila Student Profile Project (P5). The supporting factors for implementing the independent curriculum are the availability of sufficient Human Resources (HR) and adequate digital access, while the inhibiting factors are internal factors: originating from student motivation and attitudes, school facilities such as teaching aids for kinesthetic learning styles and tools. other laboratories and there is a shortage of classroom learning facilities such as LCD projectors. The impact of implementing the independent curriculum at SMA Negeri 4 Kota Bima for students is that students become focused on acquiring subjects that they have accepted and are interested in, resulting in positive things. Meanwhile, for teachers, innovation in the teaching and learning process is more enjoyable, two-way interaction will create an attitude of wanting to continue learning, looking for creative ideas and becoming more enthusiastic.